Development of Etawa Goat Milk Results in Telemung Village - Kustini Kustini; Sri Winarti; Supriyono; Alfiandi Imam Mawardi (Nusantara Science and Technology Proceedings)
Telemung Village, Pulosari Subdistrict, Banyuwangi Regency has superior commodities, one of which is in the livestock sector, namely Etawa goat cultivation. Apart from being sold from the cultivation of Etawa goats, they also raise etawa goats for milking for their milk. milk products are sold in retail form in plastic packages and sold to collectors in other villages. The packaging used is also ordinary plastic packaging and there are no innovations so that goat milk can be preferred both for the telemung village community itself and for the wider community. This is what makes goat milk products less attractive. This is an obstacle even though Etawa goat milk is more expensive than cow's milk, this is a prospect for telumung village people to increase community income. The purpose of this activity is to introduce goat milk to telemung villagers and other villages which in turn can improve the community's economy. The method used is training in making pasteurized milk by adding some flavors and training in dairy products, and counseling on how to milk the hiegins. The results of the activity showed that the community understood the stages and how to make pasteurization of goat milk with several flavors and the manufacture of candy from goat milk. Partner communities are interested in producing for sale as well as household consumption.